An accurate analytical method for the determination of cadmium: Ultraviolet based photochemical vapor generation-slotted quartz tube based atom trap-flame atomic absorption spectrophotometry. (May 2021) - Büyükpınar, Çağdaş; Bodur, Süleyman; Yazıcı, Elif; Tekin, Zeynep; San, Nevim; Tarık Komesli, Okan; Bakırdere, Sezgin
Highlights: PVG method was firstly coupled with T-SQT-AT method prior to FAAS determination. LOD and LOQ values for the proposed method were 2.5 and 8.2 µg/L, respectively. Sensitivity of the FAAS system was enhanced about 106 folds. Recovery results were ranged from 87.6 to 105.3% for the samples. Abstract: In this study, an eco-friendly and accurate analytical protocol was proposed for the determination of cadmium at trace levels. Prior to analysis in flame atomic absorption spectrophotometry (FAAS), an ultraviolet based photochemical vapor generation (PVG) method as a sample introduction system was employed to eliminate matrix effects. PVG system was combined with an online preconcentration technique called T-shaped slotted quartz tube-atom trapping (T-SQT-AT) for online preconcentration of cadmium in order to further increase analytical performance of the system. Hydrogen was used in the releasing of collected Cd atoms from the quartz surface. Under optimum conditions, limit of detection (LOD) and limit of quantitation (LOQ) of the developed method were specified as 2.5 ng/mL and 8.2 ng/mL, respectively. Percent recovery results for tap water and daphne tea samples were found to be between 87.6–105.3% and 90.9–103.3%, respectively.